Factors Affecting Poultry Meat Consumption Status and Consumption Habits of Students From Faculty of Veterinary Medicine - Akın, Ahmet Cumhur; Çevrımlı, Mustafa Bahadır; Mat, Burak; Arıkan, Mehmet Saltuk; Tekindal, Mustafa Agah (My University, 2019)
This research was carried out to in Burdur, Elazığ and Konya provinces in order to evaluate the factors affecting the poultrymeat consumption status and consumption habits of students belonging to different classes of veterinary faculties. Thematerial of the study was obtained from surveys conducted with 242 students in three different faculties during the academicyear 2018-2019. The data were analyzed by SPPS. According to the results of the research; It has been determined that 51.7%of the students are under 250 TL of the monthly individual food expenditure. The ratio of animal food expenditures inindividual food expenditures of those students to be 100 TL and below is determined as 59.1%. When the monthly poultrymeat consumption rates of the students are examined; The rate of those who did not consume was 5.8%, the rate of thoseconsuming less than 500 gr and 31% of those consuming 500-999gr was determined as 37.2%. It was determined that thestudents who participated in the survey consumed 1.1 kg of poultry meat per month. It was determined that there was nostatistically significant relationship between the poultry meat consumption and the city, class level and shelter status of thestudents. In fact, a statistically significant relationship was found between the gender, income level, monthly budget for foodand amount of monthly budget allocated to animal food
Keywords: Gıda Bilimi ve Teknolojisi; Veterinerlik